474 Predictors of Mortality, Withdrawal of Life-Sustaining Measures, and Discharge Disposition in Octogenarians With Subdural Hematomas. (1st March 2022) - Kashkoush, Ahmed; Petitt, Jordan; Ladhani, Husayn; Ho, Vanessa; Kelly, Michael L.
Abstract : INTRODUCTION: Risk factors for mortality in patients with subdural hematoma (SDH) include poor Glasgow Coma Scale (GCS), pupil non-reactivity, and hemodynamic instability on presentation. Little is published regarding prognosticators of SDH in the elderly. METHODS: A prospectively collected multi-center database of 3, 279 TBI admissions to 45 different U.S. trauma centers between 2017-2019 was queried to identify patients >79 years old presenting with SDH. Factors collected included baseline demographic data, past medical history, antiplatelet/anticoagulant use, and clinical presentation (GCS, pupil reactivity, injury severity scale [ISS]). Primary outcome data included hospital mortality/discharge to hospice care and withdrawal of life-sustaining measures. Multivariate logistic regression analyses were used to identify factors independently associated with primary outcome variables. RESULTS: A total of 695 patients were isolated for analysis. Of the total cohort, the rate of hospital mortality or discharge to hospice care was 22% (n = 150) and the rate of withdrawal of life-sustaining measures was 10% (n = 66). A multivariate logistic regression model identified GCS <13, pupil non-reactivity, increasing ISS, intraventricular hemorrhage, and neurosurgical intervention as factors independently associated with hospital mortality/hospice. Congestive heart failure (CHF), hypotension, GCS <13, and neurosurgical intervention were independently associated with withdrawal of life-sustaining measures. CONCLUSION: Poor GCS, pupil non-reactivity, ISS, and intraventricular hemorrhage are independently associated with hospital mortality or discharge to hospice care in patients >80 years with SDH. Pre-existing CHF may further predict withdrawal of lifesustaining measures.